Efektivitas Penyuluhan Kesehatan Tentang KB Intra Uterine Device (IUD) Terhadap Pengetahuan Alat Kontrasepsi IUD Pada Wanita Usia Subur Di Posyandu Kunir Putih - Meilani, Mita; Nur Insyiroh Abidah, Alief; Puji Wulandari, Risky (NHM PRESS, 2024)
Introduction: Birth control is one of the important efforts in improving reproductive health and reducing population growth rate. Among the various contraceptive methods available, the intra-uterine device (IUD) has the advantage of high effectiveness and a long period of protection. However, the use of IUDs in Indonesia is still relatively low compared to other contraceptive methods, such as injections and pills. Health counseling is one intervention that has proven effective in increasing knowledge and changing community attitudes. Various studies have shown that counseling methods that use educational media, such as leaflets, videos, and group discussions, are able to provide better understanding to women of childbearing age about the importance of IUD use.Method: This research is a quantitative study with pre- experiment design. The research design uses one group pre test and post test. Sampling using total sampling technique. The sample size in this study was 36 respondents of women of childbearing age. The intervention provided in this study was the provision of health counseling on IUD contraception and then given a questionnaire regarding contraceptive knowledge.Results: The results of this study showed that 36 respondents there was an increase in pretest and posttest knowledge scores. The results showed p- value of 0.001 (<0.05) which means Ha is accepted. Health counseling on IUD contraception increases the knowledge of women of childbearing age about IUD birth controll.Conclusion : Health counseling on IUD contraception increases the knowledge of women of childbearing age about IUD contraception.